EVALUASI IMPLEMENTASI KEBIJAKAN PROTOKOL KESEHATAN DI PASAR AIR TIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR TAHUN 2020-2021 - Annisa Nurpadila; Wazni ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The spread of the Corona Virus has reached all major cities in Indonesia, including in Kampar District, precisely in Air Tiris Village. Covid-19 cases in Air Tiris Village in September 2020 were 58 people. And keep increasing every day. This triggers a decline in the community's economy from various sectors ranging from trade, investment, tourism and others. In public places such as the Air Tiris market there are still people who do not comply with health protocols such as not wearing masks. This causes the number of Covid patients to continue to increase. To deal with the spread of covid-19 in Kampar Regency, the Kampar Regent issued regulation Number 44 of 2020 concerning the health protocol for handling Covid-19. The purpose of this study was to determine the evaluation of the implementation of health protocol policies in the Air Tiris market, and to determine the supporting and inhibiting factors for the implementation of this policy. This research uses descriptive research with a qualitative approach located in Air Tiris Village. Primary data sources were obtained from interviews, secondary data sources were obtained from documents related to the research topic. Data collection techniques obtained through interviews and documentation. The data analysis technique used is qualitative data analysis. The results of the study show that the health protocol at the Air Tiris market is guided by Regent Regulation Number 44 of 2020 concerning the application of discipline and law enforcement of health protocols. Departing from this policy, the evaluation indicators discussed in this study include effectiveness, efficiency, alignment, accuracy, adequacy, and responsiveness. In implementing the health protocol policy, there are supporting factors, namely the participation of all relevant stakeholders, the community, ministries/agencies, the TNI/Polri. While the inhibiting factor is the level of community compliance that differs in carrying out the Covid-19 health protocol. Keywords: Effectiveness, Efficiency, Alignment, Accuracy, Adequacy, Responsiveness